The Grand Escape : The Greatest Prison Breakout of the 20th Century - Bascomb, Neal (New York Arthur A. Levine Books/Scholastic Inc., 2018)
"The story of a group of Allied POWs in WWI who dared to escape from Germany's most notorious prison camp, Holzminden"--Provided by publisher.
Includes bibliographical references (pages 241-247) and index.
Keywords: World War, 1914-1918 -- Juvenile literature. -- Prisoners and prisons, German; Prisoner-of-war escapes -- Juvenile literature. -- Germany; Prisoners of war -- Biography -- Germany; Prisoners of war -- Biography -- Great Britain; World War, 1914-1918 -- Prisoners and prisons, German; Prisoner-of-war escapes; Prisoners of war